Evaluation of black tea gel and its protection potential against UV - (:unkn) unknown (My University, 2007)
In this study, aqueous and alcoholic extracts of black tea were obtained. The black tea extracts were tested in vitro for their ultraviolet (UV) absorption profile. It was found that both extracts showed UV absorption and followed the same path based on the wavelength. Aqueous extract showed a stronger absorptivity per weight basis than the alcoholic extract of black tea. A peak was obtained between 250 and 300 nm. After 300 nm, UV absorption decreased fast towards 400 nm with a low absorptivity. The black tea aqueous extract was formulated as a gel with the help of a carbomer resin and tested in vivo in six subjects for evaluating its protection potential against the UV (200-400 nm) using an artificial UV source consisting of a high pressure metal halide discharge lamp. Based on erythema evaluation, it was found that erythema appeared after 4 h and reached a peak at 24 h on control site. On the contrary, no erythema was observed in any of the six subjects on black tea gel applied sites. Therefore, it was concluded that black tea gel protected the skin from a broad range UV (200-400 nm) radiation. The black tea gel can be safely applied in large amounts on large skin surfaces without any toxicological concerns. © 2007 The Authors.
Keywords: Black tea extract; Carbomer gel; Erythema; In vivo tests; UV radiation